(Ø§Ù„Ù‚ÙˆØ§Ø¹Ø¯Ø© Ø§Ù„ÙÙ‚Ù‡ÙŠØ© Ø§Ù„Ù…Ø³ØªØ®Ø±Ø¬Ø© Ù…Ù† ÙƒØªØ§Ø¨ Ø¹Ø¯Ø© Ø§Ù„Ø¨Ø±ÙˆÙ‚ Ùˆ ÙØ±ÙˆÙ‚Ù‡Ø§ Ù„Ù„Ø¥Ù…Ø§Ù… Ø§Ù„ÙˆÙ†Ø´Ø±ÙŠØ³ÙŠ (ÙƒØªØ§Ø¨ Ø§Ù„Ø£Ù‚Ø¶ÙŠØ© ÙˆØ§Ù„Ø´Ù‡Ø§Ø¯Ø© ÙˆØ§Ù„Ø¯Ø¹Ø§ÙˆÙ‰ Ù†Ù…ÙˆØ°Ø¬Ø§ - Fakhrurrazi Muhammad Yunus (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2014)
In the Jurisprudence we find a wide range of legal issues, some of which exist in the form and `illatnya same, resulting in the same law. On the other hand there are other problems that are similar in shape and `illatnya but produces a different law. In the discussion fiqhiyyah Qaeda, it is known as Al Furuq (difference/exception). This paper is the result of the study authors to some Furuq fiqh rules contained in the book `Iddat Al Imam Al Wansyarisi Buruq bouquet. The object of study is partly Furuq fiqh rules contained in chapter Qadha, testimony and indictment. The systematics of the discussion is the author will explain some Furuq- Furuq which have been of the chapters, and then explain in detail the problem-the problem, and then deduce the rules resulting from the discussion of the Furuq Furuq